Angiotensin-(1-7) Protects against the Development of Aneurysmal Subarachnoid Hemorrhage in Mice. Issue 7 (July 2015) - Shimada, Kenji; Furukawa, Hajime; Wada, Kosuke; Wei, Yuan; Tada, Yoshiteru; Kuwabara, Atsushi; Shikata, Fumiaki; Kanematsu, Yasuhisa; Lawton, Michael T; Kitazato, Keiko T; Nagahiro, Shinji; Hashimoto, Tomoki
Angiotensin-(1-7) (Ang-(1-7)) can regulate vascular inflammation and remodeling, which are processes that have important roles in the pathophysiology of intracranial aneurysms. In this study, we assessed the effects of Ang-(1-7) in the development of intracranial aneurysm rupture using a mouse model of intracranial aneurysms in which aneurysmal rupture (i.e., aneurysmal subarachnoid hemorrhage) occurs spontaneously and causes neurologic symptoms. Treatment with Ang-(1-7) (0.5 mg/kg/day), Mas receptor antagonist (A779 0.5 mg/kg/day or 2.5 mg/kg/day), or angiotensin II type 2 receptor (AT2R) antagonist (PD 123319, 10 mg/kg/day) was started 6 days after aneurysm induction and continued for 2 weeks. Angiotensin-(1-7) significantly reduced the rupture rate of intracranial aneurysms without affecting the overall incidence of aneurysms. The protective effect of Ang-(1-7) was blocked by the AT2R antagonist, but not by the Mas receptor antagonist. In AT2R knockout mice, the protective effect of Ang-(1-7) was absent. While AT2R mRNA was abundantly expressed in the cerebral arteries and aneurysms, Mas receptor mRNA expression was very scarce in these tissues. Angiotensin-(1-7) reduced the expression of tumor necrosis factor-α and interleukin-1β in cerebral arteries. These findings indicate that Ang-(1-7) can protect against the development of aneurysmal rupture in an AT2R-dependent manner.